2021
DOI: 10.1155/2021/6699808
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis‐Related Genes Serve as Potential Prognostic Biomarkers in Clear Cell Renal Cell Carcinoma

Abstract: Metabolic rearrangement is a marker of cancer that has been widely studied in recent years. One of the major metabolic characteristics of tumor cells is the high levels of glycolysis, even under aerobic conditions, a phenomenon that is called the “Warburg effect.” We investigated the expression and copy number variation (CNV) frequency of all glycolysis-related genes in multiple cancer types and found many differentially expressed genes, particularly in clear cell renal cell carcinoma (ccRCC). Single nucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…2OGDH is decreased in CKD induced by high-salt diet and aristocholic acid administration [ 22 , 115 ], as has been reported in non-diabetic CKD patients [ 42 ]. On the other hand, in RCC 2OGDH lower expression was associated with poor outcome [ 116 ]. Together, this indicates a decreased synthesis of succinyl-CoA in some progressive kidney diseases.…”
Section: Succinyl-coamentioning
confidence: 99%
“…2OGDH is decreased in CKD induced by high-salt diet and aristocholic acid administration [ 22 , 115 ], as has been reported in non-diabetic CKD patients [ 42 ]. On the other hand, in RCC 2OGDH lower expression was associated with poor outcome [ 116 ]. Together, this indicates a decreased synthesis of succinyl-CoA in some progressive kidney diseases.…”
Section: Succinyl-coamentioning
confidence: 99%
“…Glucose-6-phosphate dehydrogenase (G6PD) serves as a pacemaker of PPP due to its activity to shunt glucose flux to PPP and catalyze the first and rate-limiting step of PPP (17). Mounting evidence indicated that increased glucose flux towards PPP and overactivation of G6PD are common in many cancer types, including clear cell renal cell carcinoma, hepatocellular carcinoma, colorectal cancer, prostate cancer, and ESCC (23)(24)(25)(26)(27). It is known that G6PD overactivation in tumor cells is regulated at the transcriptional or posttranslational level (17,21,22,(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that NUP43 plays the role of promoter in the progression of tumors [ 43 ]. Yan Zhang et al developed glycolysis-related genes to predict the outcomes of patients in clear cell renal cell carcinoma (ccRCC); PGK1 is one of these genes, whose high expression predicted poor prognosis in patients with ccRCC [ 44 ]. PGK1 expression was also significantly increased in BC tissues and associated with HER2+ and positive status of ER [ 45 ].…”
Section: Discussionmentioning
confidence: 99%